Clinical outcome of patients with venous thromboembolism and renal insufficiency - Falgá, Conxita; Capdevila, Josep Antón; Soler, Silvia; Rabuñal, Ramón; Muñoz-Torrero, Juan Francisco Sánchez; Gallego, Pedro; Monreal, Manuel; the RIETE Investigators (Thrombosis and Haemostasis, 2007)
There is little information on the clinical outcome of patients with venous thromboembolism and renal insufficiency. RIETE is an ongoing, prospective registry of consecutive patients with acute, objectively confirmed, symptomatic deep vein thrombosis (DVT) or pulmonary embolism (PE). In this analysis we analyzed the three-month outcome in patients with creatinine clearance (CrCl) <30 ml/min. As of March 2007, 1,037 of the 18,251 (5.7%) patients enrolled in RIETE had CrCl <30 ml/min. During the three-month study period these patients had an increased incidence of fatal bleeding, fatal PE, and overall death compared to those with CrCl >30 ml/min. Of the 579 patients presenting with clinically overt PE, 52 (9.0%) died of the initial PE, 13 (2.2%) of recurrent PE, and nine (1.6%) died of bleeding complications. During the first 15 days of therapy the 10% incidence of fatal PE was 10-fold their 1.0% of fatal bleeding. From day 16 to 90, the 1.0% rate of fatal PE was not significantly higher than the 0.5% of fatal bleeding. Of the 458 DVT patients with CrCl <30 ml/min, 14 (3.1%) had fatal bleeding and only one (0.2%) died of PE. In patients with CrCl <30 ml/min presenting with clinically overt PE the main threat is PE itself. On the contrary, in those with DVT the main threat is bleeding.
Keywords: Venous thromboembolism; renal insufficiency; anticoagulant therapy